START Triage Scale in Disasters - Galip Usta; Kemal Torpuş; Uçar Küçük (Doğal Afetler ve Çevre Dergisi)
Disasters are events that occur since the beginning of time. When previous records are investigated, information on various types of disasters occurred in different parts of the World are encountered. Disasters occur unexpectedly and require constant state of preparedness. No matter how extensive the precautions are, disasters cannot be prevented, but the precautions significantly contribute to the reduction of negative consequences to a minimum. In this context, response plans to events that may occur are as important as the preparedness plans. Responding to disaster victims on time, correctly and efficiently reduces the mortality rate to a minimum as well as increasing the survival rate. Correct classification of the victims based on the life threatening events or the priority of their injuries, providing transport, and ensuring each individual receives emergency aid should be the main goals of triage. That is, to be the most helpful to as many injured people as one can by using the limited opportunities available. A successfully performed triage not only increases the success of the healthcare team’s response, it also enables healthy execution of scene management. In this study, the aim is to provide information about START scale composed of the first letters of “Simple Triage And Rapid Treatment” that has been developed and accepted to be used in mass events.